State Sovereignty And Territorial Boundaries In The Perspective Of International Law - Andre Kurniawan (PT. Hafasy Dwi Nawasena, 2026)
: State sovereignty is a fundamental principle of international law, grounded in the existence of clearly defined and legally recognized territory. The determination of land, maritime, and air boundaries is essential for safeguarding territorial integrity, national security, and peaceful interstate relations. Nevertheless, border disputes frequently arise due to conflicting interpretations of international treaties, ambiguous territorial delimitations, colonial legacies, geographical changes, and competing political and economic interests, posing significant challenges to regional and global stability. This study aims to examine the concept of state sovereignty under international law, analyze legal mechanisms for determining state boundaries, and identify the causes and resolution of border disputes resulting from treaty interpretation. Using normative legal research with legislative, conceptual, and case study approaches, the study analyzes primary, secondary, and tertiary legal materials through qualitative methods. The findings indicate that international law provides a comprehensive framework for boundary determination through international treaties, customary international law, judicial decisions, and the provisions of the United Nations Convention on the Law of the Sea (UNCLOS). Border disputes may be resolved through negotiation, mediation, arbitration, or adjudication before the International Court of Justice. The study concludes that legal certainty over territorial boundaries is indispensable for the effective exercise of state sovereignty. Strengthened international cooperation, harmonized treaty interpretation, and more effective dispute resolution mechanisms are therefore essential to promote international peace, stability, and sustainable interstate relations